Selected Single Meters of Prosody - Dr Mubshar Saeed (Zaban-o-Adab, 2025)
The study of Arabic literary sciences encompasses various fields, including morphology, syntax, rhetoric, etymology, theology, logic, philosophy, history, linguistics , jurisprudence, and hadith. One significant branch among these is the science of prosody, known as "arood" in Arabic, equivalent to "prosody" in English. It refers to the rules and principles governing the structure and rhythm of poetry. Prominent lexicographers like Shan-ul-Haq Haqqi, Ahmad Dehlvi, and Muhammad Abdullah Kheshgi have defined it in various ways. The renowned scholar Khalil bin Ahmad al-Farahidi, credited as the founder of this science, developed the system of poetic meters, which has been elaborated upon by numerous scholars and experts over time. This paper reviews definitions and explanations from different sources, emphasizing the significance of a comprehensive understanding of prosody in distinguishing between well-structured and poorly structured poetry, serving as the "science of metrics" in the field of literary arts.